EFFECT OF COMPETENCY-BASED RECRUITMENT AND TRAINING ON EMPLOYEE PERFORMANCE IN INDONESIAN MANUFACTURING COMPANIES - Mochamad Gilang Ginandjar (RADJA PUBLIKA, 2025)
This study explores the effect of competency-based recruitment and training on employee performance in Indonesian manufacturing companies, utilizing a qualitative approach through a comprehensive literature review. As the manufacturing sector continues to play a crucial role in Indonesia's economic growth, understanding the factors that enhance employee performance is essential. The research synthesizes various scholarly articles, reports, and case studies to identify key competencies that contribute to effective recruitment and training processes. Findings indicate that competency-based recruitment not only aligns employee skills with organizational needs but also fosters a culture of continuous improvement and adaptability. Additionally, targeted training programs that focus on the development of specific competencies significantly enhance employee performance, leading to increased productivity and job satisfaction. The study highlights the importance of integrating competency frameworks into recruitment strategies and training modules to create a skilled workforce capable of meeting the challenges of a competitive manufacturing landscape. Furthermore, it emphasizes the need for ongoing evaluation and adjustment of these processes to ensure their effectiveness in driving employee performance. The insights gained from this research provide valuable implications for human resource management practices in the manufacturing sector, suggesting that organizations that prioritize competency-based approaches are more likely to achieve sustainable performance outcomes.